Needs Analysis: Website-Based Mental Health Literacy Scale for High School Students - Exzan Abdi Fariz; Yosef Yosef; Sardianto Markos Siahaan (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
The rapid development of digital technology has transformed psychological assessment practices in education, including guidance and counseling services in high schools. However, mental health assessments in schools are still largely conducted manually, limiting efficiency, data integration, and timely intervention. This study aims to analyze the need for developing a web-based mental health literacy scale for high school students by examining four main components: student needs, school counselor needs, scale characteristics, and counseling service needs. A descriptive qualitative approach was employed using observations, semi-structured interviews, and a needs analysis questionnaire. Participants included 1,000 high school students and 20 school counselors in Palembang and its surrounding areas. The results showed that most need components were rated at high to very high levels. Students expressed strong expectations for digital assessment instruments that are accessible, relevant, stigma-sensitive, and user-friendly, while school counselors emphasized the importance of technological support, the availability of structured data, and strong psychometric quality. Furthermore, the need for counseling services highlights the urgency of integrating assessment, digital counseling services, early detection, school collaboration, and data-driven evaluation. These findings underscore the need to develop a web-based mental health literacy scale as part of an integrated digital counseling system to support effective, evidence-based, and responsive mental health services in schools.